Sustaining surveillance as an intervention during the COVID-19 pandemic in Cabo Verde and implications for malaria elimination - DePina, Adilson; Barros, Helga; Tiffany, Amanda; Stresman, Gillian (Frontiers in Immunology, 2022)
Cabo Verde reported the first case of COVID-19 on March 19, 2020. Containment measures were quickly implemented and over 80,000 COVID-19 tests were performed in 2020 with 11,840 confirmed infections (2% of the population) and 154 deaths. In a setting where the last locally acquired malaria case was reported in January 2018, any interruptions to malaria care-seeking have the potential for infections to go untreated and transmission re-establishing. This work aims to determine whether there was any change in the number of people seeking care or being tested for malaria and, using an interrupted time series analysis, identify if any change was associated with COVID-19 interventions implemented. Routinely collected surveillance data for outpatient attendance and testing for malaria and COVID-19 were aggregated per month for each health facility (outpatient and malaria) or per municipality (COVID-19) from 2017 to 2020. The timeline of COVID-19 interventions was generated based on when and where interventions were implemented. Results show that there was a marked shift in care-seeking in Cabo Verde. The mean observed outpatient attendance dropped from 2,057 visits per month between January 2017 and March 2020 to 1,088 between April to December 2020, or an estimated 28% reduction compared to expected trends during the pre-pandemic period. However, malaria testing rates per 1,000 outpatients after the pandemic began increased by 8% compared to expected trends. Results suggest that the pandemic impacted care-seeking but led to a non-significant increase in testing for malaria per 1,000 outpatient consultations. With the cessation of international travel, the risk of imported infections seeding new transmission declined suggesting the risk of undetected transmission is low. It is important for countries to understand their specific malaria risks and vulnerabilities in order to ensure the achievements made to interrupt malaria transmission can be sustained.